Laxative effect of mulberry ferment on two models of constipated mice - Yanghang He; Gang Liu; Chen Xia; Jian Chen; Jiayuan Zhao; Xueli Li; Junlin Deng; Xueli Wang; Zhuoya Xiang; Peng Zeng (Journal of Functional Foods, 2022)
This study was to probe the effects of mulberry ferment on constipation (induced by diphenoxylate or loperamide) in mice. Herein, several bioactive substances and antioxidant activities of mulberry ferment were measured, and their effects on defecation, histological structure of ileum and intestinal microflora were investigated. During fermentation, total polyphenols, and flavonoids were increased while the antioxidant activities increased by a large extent. In animal experiments, diphenoxylate caused more serious injuries than loperamide did, and diphenoxylate kept the more unfavorable gut microbiological environment compared with loperamide. Administration of mulberry ferment can increase the fecal moisture content, shorten the first black fecal defecation time, and accelerate the gastro-intestinal transit. Besides, mulberry ferment alleviated ileal tissue organ injuries caused by constipation, suppressed the level of Oscillibacter and Desulfovibrio and increased the Bacteroidales and Bacteroidales_S24-7. In summary, mulberry ferment could be considered as a promising functional food because of their good alleviation on constipation.